The year the gypsies came - Glass, Linzi 1966- (H. Holt, 2006)
In Johannesburg, South Africa, in the late 1960s, twelve-year-old Emily, who longs for affection from her quarreling parents, finds comfort in the stories of a Zulu servant and in her friendship with a young houseguest who has an equally troubled family.
hier auch später ersch., unveränd. Nachdr.
Keywords: Geschichte 1900-2000; Geschichte; Family problems -- Fiction; Apartheid -- Fiction; Südafrika (Staat); Johannesburg (South Africa) -- History -- 20th century -- Fiction; South Africa -- History -- 1961-1994 -- Fiction; Jugendbuch; Domestic fiction; Young adult fiction